Advancing sustainable juice processing through thermosonication: functional enrichment of apple juice with pollen - Seydi Yıkmış; Melikenur Türkol; Nazan Tokatlı Demirok; Berna Al; Isam A. Mohamed Ahmed; Moneera O. Aljobair (Frontiers in Sustainable Food Systems)
The development of functional beverages requires the use of sustainable technologies to increase both nutritional value and consumer appreciation. This study aims to investigate the effects of thermosonication, a sustainable food processing approach, on Uruset apple juice to produce a functional beverage enriched with pollen. In the study, four process parameters—temperature, time, amplitude, and pollen concentration—were optimized. As a result of the experimental design using response surface methodology (RSM), significant increases were observed in total phenolic substance (TPC), total flavonoid (TFC), and antioxidant capacity [DPPH (2,2-diphenyl-1-picrylhydrazyl) and CUPRAC (copper reducing antioxidant capacity)] values. At the same time, significant improvements were observed in the content of phenolic compounds, including chlorogenic acid, gallic acid, quercetin, and catechin. Thermosonication process partially suppressed the enzymatic activity (PPO) and ensured the preservation of phenolic compounds and positively affected the shelf life of the product. Sensory analysis results showed that apple pollen juice processed with thermosonication received higher scores in terms of taste, odor, and general liking compared to both the control and pasteurized groups. Optimum process conditions were determined to be 40.9°C temperature, 5.63 min process time, 61.01% amplitude, and 60 mg/100 mL pollen. The findings reveal that a sustainable, functional beverage with enhanced nutritional and sensory quality can be developed through the synergistic effect of thermosonication and a natural pollen additive. This approach offers an innovative and environmentally friendly solution that can be applied on an industrial scale as an alternative to traditional heat treatments. In the future, the production of functional beverages supported by innovative processes such as thermosonication could help to promote healthier and more environmentally friendly products within the food industry.